2014
DOI: 10.1007/s13762-014-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of street environments on fuel efficiency: insights from naturalistic driving

Abstract: Fuel consumption and greenhouse gas emissions in the transportation sector are a result of a ''threelegged stool'': fuel types, vehicle fuel efficiency, and vehicle miles travelled (VMT). While there is a substantial body of literature that examines the connection between the built environment and total VMT, few studies have focused on the impacts of the street environment on fuel consumption rate. Our research applied structural equation modeling to examine how driving behaviors and fuel efficiency respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The gender ratio is more easily measured. We included this measure because previous studies have suggested that males prefer to drive [72], so the gender ratio (male/female) can reflect the influence of social factors on PM 2.5 concentrations through travel type. Data was sourced from the Sixth Census Data of Shanghai Jiedao in 2010 (http://www.stats.gov.cn/tjsj/tjgb/rkpcgb/dfrkpcgb/ 201202/t20120228_30403.html).…”
Section: Measurement Of Variables and Datamentioning
confidence: 99%
“…The gender ratio is more easily measured. We included this measure because previous studies have suggested that males prefer to drive [72], so the gender ratio (male/female) can reflect the influence of social factors on PM 2.5 concentrations through travel type. Data was sourced from the Sixth Census Data of Shanghai Jiedao in 2010 (http://www.stats.gov.cn/tjsj/tjgb/rkpcgb/dfrkpcgb/ 201202/t20120228_30403.html).…”
Section: Measurement Of Variables and Datamentioning
confidence: 99%
“…However, even low vehicle emissions may yield high concentrations in particular areas because emissions may disperse and react to the influence of other factors (Civerolo et al 2007; Hang et al 2009; Buccolieri, Sandberg, and Di Sabatino 2010; Schweitzer and Zhou 2010). Additionally, a recent study shows that compact urban form may be associated with lower driving speeds, more speed changes, lower fuel efficiencies, and higher emission rates in spite of lower vehicle miles traveled (X. Wang et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most reports conclude that there is a negative correlation between employment density and TCE [ 44 , 86 , 87 ]. Wang et al found that an increase in employment density helps to reduce the average speed of vehicles, increase fuel efficiency, and reduce transportation energy consumption [ 105 ]. Nevertheless, some reports have raised questions about this opinion [ 90 , 106 ].…”
Section: Resultsmentioning
confidence: 99%